Determinants of Displaced Commercial Risk in Islamic Banking Institutions: Malaysia Evidence - Arshad, Noraziah Che; Zakaria, Roza Hazli; Sulaiman, Ahmad Azam; Irijanto, Tubagus Thresna (Jurnal Trikonomika, 2014)
Islamic banks are exposed to a unique risk such as Displaced Commercial Risk (DCR). DCR arises from the assets managed on behalf of the investment account holders which may be borne by the Islamic bankâs own capital, when the Islamic banks forgo part or all of its share of profits on the investment account holders funds, in order to increase the return to the investment account holders. In a dual banking system, DCR could be a threat to the Islamic banks given the competition of fixed and higher return from the conventional banks. However, DCR would not be a threat to Islamic banks if their account holders choose Islamic banks due to religious obligatory factor. Pertaining to this issue, this paper aims to identify the determinants of factors influencing the DCR among the Islamic banks in the case of Malaysia. Results of the study suggest that the DCR is significantly determined by the Investment account holder funds, Islamic deposit, rate of return, and interest rate.